An electrode sheet and a battery
Patent Information
- Application Number
- CN202611300992.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-26
- Publication Date
- 2026-10-16
AI Technical Summary
然而,此类工艺条件在提升电池容量的同时,也引发了粘结剂上浮现象,即因极片表面温度高于内部形成溶剂浓度梯度,导致粘结剂从极片内部向表面迁移并富集,形成活性层顶部粘结剂过量、底层严重匮乏的结构失衡
[0020] This application provides an electrode sheet and a battery. The electrode sheet includes a current collector and an active layer disposed on the surface of the current collector. The active layer includes an active material and a binder. Along the direction from the active layer to the current collector, the active layer on the surface of the current collector is subjected to n peeling processes until the thickness of the remaining active layer on the surface of the current collector is less than or equal to 15 μm. The peeling force F1 measured in the first peeling process and the peeling force F2 measured in the nth peeling process are obtained. n The thickness of the active layer removed in each stripping process is between 8 μm and 12 μm, and n ≥ 3; Calculate R = F1/F n And the peel force attenuation slope α=|(F n -F1)/(n-1)|, R satisfies: 1≤R≤4, and/or, α satisfies: 0.2≤α≤20. This can improve the dispersion of the binder in the electrode sheet and improve the cycle performance of the battery.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This application relates to the field of batteries, and more particularly to an electrode sheet and a battery. Background Technology
[0002] With the continuous improvement of battery energy density, thick electrodes (positive electrode surface density > 200g / m²) are becoming increasingly important. 2 Negative electrode >100g / m 2 Rapid drying processes (coating speed > 10 m / min, baking temperature > 100℃) are gradually becoming the mainstream processes in the industry. However, while these process conditions improve battery capacity, they also cause binder buoyancy. This occurs because the surface temperature of the electrode is higher than the internal temperature, creating a solvent concentration gradient that causes the binder to migrate and accumulate from the inside of the electrode to the surface. This results in a structural imbalance with excessive binder at the top of the active layer and a severe lack of binder at the bottom. This imbalance directly weakens the mechanical integrity of the electrode (e.g., decreased peel strength of the bottom layer, increased powder shedding rate during rolling) and induces safety and performance risks such as uneven deposition of active ions at the electrode and electrolyte interface, active ion precipitation, and cycle degradation.
[0003] Therefore, existing technologies generally do not have the problem of poor battery cycle performance caused by the binder floating on the electrode sheet, which urgently needs to be solved. Summary of the Invention
[0004] This application provides an electrode sheet and a battery that can improve the dispersibility of the binder in the electrode sheet, thereby improving the cycle performance of the battery.
[0005] In a first aspect, embodiments of this application provide an electrode sheet, the electrode sheet comprising a current collector and an active layer disposed on the surface of the current collector, the active layer comprising an active material and an adhesive, wherein the active layer on the surface of the current collector is subjected to n peeling processes along the direction from the active layer to the current collector until the thickness of the remaining active layer on the surface of the current collector is less than or equal to 15 μm, and the peeling force F1 measured in the first peeling process and the peeling force F2 measured in the nth peeling process are obtained. n In each peeling process, the thickness of the active layer removed is between 8 μm and 12 μm, and n ≥ 3; the peeling force difference coefficient of the active layer is obtained as R = F1 / F. n And the peel force attenuation coefficient α=|(F n -F1) / (n-1)|, the peel force difference coefficient R satisfies: 1≤R≤4, and / or, the peel force attenuation coefficient α satisfies: 0.2≤α≤20.
[0006] In one possible implementation, the areal density of the electrode sheet on one side is 80 g / m². 2 ~260g / m 2 .
[0007] In one possible implementation, the active material is at least one of a positive electrode active material and a negative electrode active material; preferably, the positive electrode active material includes one or more of lithium iron phosphate, lithium nickel cobalt manganese oxide, and lithium cobalt oxide; and / or, the negative electrode active material includes one or more of graphite and silicon-based materials.
[0008] In one possible implementation, the negative electrode active material comprises the graphite and the silicon-based material, wherein the mass ratio of the graphite to the silicon-based material is (85~95):(5~15).
[0009] In one possible implementation, the active material is a positive electrode active material, 1≤R≤4, and 0.2≤α≤20.
[0010] In one possible implementation, the active material is a negative electrode active material, where 1.2 ≤ R ≤ 4 and 1.2 ≤ α ≤ 8.
[0011] In one possible implementation, the active material is a positive electrode active material, and the single-sided areal density of the electrode sheet is 160 g / m². 2 ~260g / m 2 .
[0012] In one possible implementation, the active material is a negative electrode active material, and the surface density of the electrode sheet on one side is 80 g / m². 2 ~160g / m 2 .
[0013] Secondly, embodiments of this application provide a battery including the electrode sheets described above.
[0014] In one possible implementation, the electrode sheet is at least one of a positive electrode sheet and a negative electrode sheet. The positive electrode sheet includes a positive active layer, which includes a positive active material. The negative electrode sheet includes a negative active layer, which includes a negative active material.
[0015] When the positive electrode active material is lithium iron phosphate and the negative electrode active material is graphite: the capacity retention rate of the battery after 500 cycles is y1 = k1 × R1 + A1, where k1 is -2.2 ~ -1.7, R1 is the peeling force difference coefficient of the positive electrode active layer, and A1 is 99.8 ~ 101.5;
[0016] Alternatively, when the positive electrode active material is lithium nickel cobalt manganese oxide and the negative electrode active material is graphite: the capacity retention rate of the battery after 500 cycles is y2 = k2 × R2 + A2, where k2 is -3.0 ~ -2.6, R2 is the peeling force difference coefficient of the positive electrode active layer, and A2 is 91.2 ~ 95.8;
[0017] Alternatively, when the positive electrode active material is lithium cobalt oxide and the negative electrode active material is graphite: the capacity retention rate of the battery after 500 cycles is y3 = k3 × R3 + A3, where k3 is -3.8 to -3.1, R3 is the peeling force difference coefficient of the positive electrode active layer, and A3 is 88.2 to 94.1.
[0018] Alternatively, when the positive electrode active material is lithium nickel cobalt manganese oxide and the negative electrode active material is silicon-based material and graphite: the capacity retention rate of the battery after 500 cycles is y4 = k4 × R4 + A4, where k4 is -5.5 to -4.6, R4 is the peeling force difference coefficient of the negative electrode active layer, and A4 is 89.7 to 94.4.
[0019] Alternatively, when the positive electrode active material is lithium iron phosphate and the negative electrode active material is graphite: the capacity retention rate of the battery after 500 cycles is y5 = k5 × R5 + A5, where k5 is -2.3 to 1.8, R5 is the peeling force difference coefficient of the negative electrode active layer, and A5 is 98.3 to 101.5.
[0020] This application provides an electrode sheet and a battery. The electrode sheet includes a current collector and an active layer disposed on the surface of the current collector. The active layer includes an active material and a binder. Along the direction from the active layer to the current collector, the active layer on the surface of the current collector is subjected to n peeling processes until the thickness of the remaining active layer on the surface of the current collector is less than or equal to 15 μm. The peeling force F1 measured in the first peeling process and the peeling force F2 measured in the nth peeling process are obtained. n The thickness of the active layer removed in each stripping process is between 8 μm and 12 μm, and n ≥ 3; Calculate R = F1 / F n And the peel force attenuation slope α=|(F n -F1) / (n-1)|, R satisfies: 1≤R≤4, and / or, α satisfies: 0.2≤α≤20. This can improve the dispersion of the binder in the electrode sheet and improve the cycle performance of the battery. Detailed Implementation
[0021] To enable those skilled in the art to better understand the solutions of this invention, the following provides a more detailed description of this application. The specific embodiments listed below are merely descriptions of the principles and features of this invention; the examples are only for explaining the invention and are not intended to limit its scope. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without inventive effort are within the scope of protection of this invention.
[0022] In view of this, embodiments of the present invention provide an electrode sheet, the electrode sheet comprising a current collector and an active layer disposed on the surface of the current collector, the active layer comprising an active material and an adhesive, wherein the active layer on the surface of the current collector is subjected to n peeling processes along the direction from the active layer to the current collector until the thickness of the remaining active layer on the surface of the current collector is less than or equal to 15 μm, and the peeling force F1 measured in the first peeling process and the peeling force F2 measured in the nth peeling process are obtained. n In each peeling process, the thickness of the active layer removed is between 8 μm and 12 μm, and n ≥ 3; the peeling force difference coefficient of the active layer is obtained as R = F1 / F. n And the peel force attenuation coefficient α=|(F n -F1) / (n-1)|, the peel force difference coefficient R satisfies: 1≤R≤4, and / or, the peel force attenuation coefficient α satisfies: 0.2≤α≤20.
[0023] According to the inventors' research, electrode sheets with the above-mentioned characteristics can improve the dispersibility of binders in electrode sheets, thereby improving the cycle performance of batteries.
[0024] The reason for this is that the R value reflects the degree to which the binder floats from the active layer near the current collector to the active layer away from the current collector. The closer the R value is to 1, the closer the peeling force of the first peeling treatment is to the peeling force of the nth peeling treatment. This indicates that the content of binder in the active layer removed in the first peeling treatment is not much different from that in the active layer removed in the nth peeling treatment, which means that the degree of binder dispersion in the electrode sheet is better. The α value reflects the intensity of the binder migration from the active layer near the current collector to the active layer away from the current collector. A sharp increase in the α value indicates a significant decrease in the binder content. By adjusting R and α within the above range, it is shown that the binder is more uniformly dispersed in the thickness direction of the electrode sheet.
[0025] For example, R can be a range of 1, 1.2, 2, 3, 4 or any two of them; α can be a range of 0.2, 1, 1.2, 5, 8, 10, 15, 20 or any two of them.
[0026] In some embodiments, the areal density of one side of the electrode sheet is 80 g / m². 2 ~260g / m 2 For example, it can be 80g / m³. 2 120g / m 2 160g / m 2 200g / m 2 230g / m 2 260g / m 2Or a range consisting of any two of these. By improving the dispersibility of the binder in the electrode sheet and enhancing the cycle performance of the battery, the energy density of the battery can be further increased.
[0027] In some embodiments, the active material is at least one of a positive electrode active material and a negative electrode active material. That is, the electrode sheet can be at least one of a positive electrode sheet and a negative electrode sheet, meaning that the method for improving the dispersion of the binder in the electrode sheet in this application can be used for both positive and negative electrode sheets.
[0028] In some embodiments, the positive electrode active material includes one or more of lithium iron phosphate, lithium nickel cobalt manganese oxide, and lithium cobalt oxide. Because the particle size of each positive electrode active material differs, it also has different effects on the dispersion degree of the binder in the electrode sheet, which is more conducive to improving the uniformity of binder distribution in electrode sheets made of different positive electrode active materials.
[0029] In some embodiments, the negative electrode active material includes one or more of graphite and silicon-based materials, wherein the silicon-based material includes at least one of silicon-carbon composite materials, silicon oxide materials, and nano-silicon. Improving the dispersion of the binder in the electrode sheet further enhances the compatibility with different battery systems.
[0030] In some embodiments, the negative electrode active material includes graphite and silicon-based materials, with a mass ratio of graphite to silicon-based materials of (85~95):(5~15), for example, it can be a range of (85:15), (90:10), (95:5), or any combination thereof. Graphite has good conductivity and small volume expansion during charging and discharging, but its theoretical capacity is low; silicon-based materials have extremely high theoretical capacity, but their volume expansion during charging and discharging is severe. When the mass ratio of graphite to silicon-based materials is within the above range, it can improve the battery capacity and reduce the volume expansion of the negative electrode active material while mitigating the uneven distribution of binder in the electrode sheet.
[0031] In some embodiments, the active material is a positive electrode active material, 1≤R≤4, and 0.2≤α≤20.
[0032] In some embodiments, the active material is a negative electrode active material, where 1.2 ≤ R ≤ 4 and 1.2 ≤ α ≤ 8.
[0033] Specifically, the positive electrode active material particles (a few micrometers to tens of micrometers) are usually larger than the negative electrode active particles (a few micrometers). The size of the active material particles will affect the peeling force of the active layer. Therefore, the R and α of the positive electrode and the negative electrode are limited respectively to further improve the dispersion uniformity of the binder in the positive electrode and the negative electrode.
[0034] In some embodiments, the active material is a positive electrode active material, and the areal density of the electrode sheet on one side is 160 g / m². 2 ~260g / m2 For example, it can be 160g / m 2 180g / m 2 200g / m 2 220g / m 2 240g / m 2 260g / m 2 Or a range consisting of any two of these. This is more conducive to balancing the improvement of binder dispersion in the electrode sheet and the increase of battery energy density.
[0035] In some embodiments, the active material is a negative electrode active material, and the surface density of the electrode sheet on one side is 80 g / m². 2 ~160g / m 2 For example, it can be 80g / m 2 100g / m 2 120g / m 2 140g / m 2 160g / m 2 Or a range consisting of any two of these. Improving the dispersibility of the binder in the electrode sheet is more conducive to simultaneously increasing the energy density of the battery.
[0036] This invention also provides a battery comprising the electrode sheet described above. This battery has the same advantages as the electrode sheet described above, which will not be repeated here.
[0037] In some embodiments, the electrode sheet is at least one of a positive electrode sheet and a negative electrode sheet. The positive electrode sheet includes a positive active layer, which includes a positive active material; the negative electrode sheet includes a negative active layer, which includes a negative active material. In some embodiments, when the positive active material is lithium iron phosphate and the negative active material is graphite: the capacity retention rate after 500 battery cycles is y1 = k1 × R1 + A1, where k1 is -2.2 ~ -1.7, R1 is the peeling force difference coefficient of the positive active layer, and A1 is 99.8 ~ 101.5;
[0038] In some embodiments, when the positive electrode active material is lithium nickel cobalt manganese oxide and the negative electrode active material is graphite: the capacity retention rate after 500 battery cycles is y2 = k2 × R2 + A2, where k2 is -3.0 ~ -2.6, R2 is the peeling force difference coefficient of the positive electrode active layer, and A2 is 91.2 ~ 95.8.
[0039] In some embodiments, when the positive electrode active material is lithium cobalt oxide and the negative electrode active material is graphite: the capacity retention rate after 500 battery cycles is y3 = k3 × R3 + A3, where k3 is -3.8 to -3.1, R3 is the peeling force difference coefficient of the positive electrode active layer, and A3 is 88.2 to 94.1.
[0040] In some embodiments, when the positive electrode active material is lithium nickel cobalt manganese oxide and the negative electrode active material is silicon-based material and graphite: the capacity retention rate after 500 battery cycles is y4 = k4 × R4 + A4, where k4 is -5.5 to -4.6, R4 is the peeling force difference coefficient of the negative electrode active layer, and A4 is 89.7 to 94.4.
[0041] In some embodiments, when the positive electrode active material is lithium iron phosphate and the negative electrode active material is graphite: the capacity retention rate after 500 battery cycles is y5 = k5 × R5 + A5, where k5 is -2.3 to -1.8, R5 is the peeling force difference coefficient of the negative electrode active layer, and A5 is 98.3 to 101.5.
[0042] By correlating the cycle performance of each battery system with R, it is easier to quickly and directly determine the battery cycle performance. Compared with conventional evaluation methods, it is not necessary to assemble the electrode sheets into a battery and perform electrochemical cycling to determine the battery cycle performance, which greatly shortens the testing cycle.
[0043] The existing technology fails to limit the thickness of the active layer removed in each peeling process used to test the peel force, which makes it impossible to directly establish the correspondence between the electrode thickness and the degree of adhesive dispersion, and fails to provide qualitative data, and cannot achieve multi-dimensional quantification of the degree of adhesive dispersion (such as significance, migration intensity and risk level).
[0044] The inventors discovered that by limiting the thickness of the active layer removed in each peeling process to between 8μm and 12μm, the peeling force of each peeling process can be tested. By combining a dual-parameter quantification system of the adhesive dispersion degree significance and the peeling force decay slope, the non-uniformity of the adhesive dispersion degree along the active layer thickness direction can be reflected.
[0045] In view of this, embodiments of the present invention provide a method for testing the degree of adhesive dispersion in an electrode sheet. The electrode sheet includes a current collector and an active layer disposed on the surface of the current collector. The active layer includes an active material. The testing method includes the following steps: performing n peeling treatments on the active layer on the surface of the current collector along the direction from the active layer to the current collector until the thickness of the remaining active layer on the surface of the current collector is less than or equal to 15 μm, and obtaining the peeling force F1 measured in the first peeling treatment and the peeling force F2 measured in the nth peeling treatment. n The thickness of the active layer removed in each stripping process is between 8 μm and 12 μm, and n ≥ 3; Calculate R = F1 / F n And the peel force attenuation slope α=|(F n -F1) / (n-1)|, the degree of binder dispersion in the electrode sheet is determined according to R and α.
[0046] According to the inventors' research, the above-mentioned test method for the degree of binder dispersion in the electrode sheet can test the degree of binder dispersion in the electrode sheet. By adjusting the thickness of the active layer removed in each peeling process to be between 8μm and 12μm, the accuracy of the degree of binder dispersion along the direction from the active layer to the current collector is improved. At the same time, the R value can reflect the degree to which the binder floats from the active layer near the current collector to the active layer away from the current collector. The closer the R value is to 1, the better the degree of binder dispersion in the electrode sheet. The α value can reflect the intensity of the binder migration from the active layer near the current collector to the active layer away from the current collector. A sharp increase in the α value indicates a significant decrease in binder content and concentration at weak interfaces. The dual-parameter system of R value and α value determines the degree of binder dispersion in the electrode sheet.
[0047] Furthermore, the above-mentioned method for testing the degree of adhesive dispersion in the electrode sheet does not require scraping, adding additional solvents for treatment or high-temperature treatment. It directly characterizes the adhesive distribution through peel force testing, preserving the integrity of the electrode sheet. At the same time, the peeling time for each peeling process is less than or equal to 180 seconds, which helps to improve testing efficiency.
[0048] For example, the thickness of the active layer removed in each stripping process can be 8 μm, 9 μm, 10 μm, 11 μm, 12 μm or any combination thereof; n can be 3, 4, 5, 6, 7, 8, 9, 10, 11 or any combination thereof, and the thickness of the remaining active layer on the current collector surface can be 3 μm, 5 μm, 7 μm, 9 μm, 11 μm, 13 μm, 15 μm or any combination thereof.
[0049] Specifically, the thickness of any two peels can be the same or different, but both are between 8μm and 12μm; the nth peeling process is the last peeling process.
[0050] Specifically, the peeling force mentioned above refers to the 180° peeling force. It can be understood as the tensile force value collected during the peeling process when the electrode sheet is peeled once by a universal tensile testing machine. The tensile force-displacement curve is obtained, and the average value of the peeling data with the most stable tensile force-displacement curve is the peeling force.
[0051] In this embodiment of the invention, the thickness of the active layer removed in each peeling process can be measured by the following method: take the tape before the test and measure the thickness of the tape as L1. After the peeling process, take the tape after each peeling process (at this time, the active layer that has been peeled off is attached to the tape) and measure its overall thickness as L2. Then the thickness of the active layer removed in each peeling process = L2 - L1. The thickness can be measured by a thickness gauge.
[0052] In some embodiments, each peeling process includes: attaching adhesive tape to the surface of the active layer facing away from the current collector, then performing a peel force test to complete the peeling process and measure the peel force; wherein, in each peeling process, the adhesive tape used meets the following requirements: the tape includes an adhesive layer, and when the active material is lithium iron phosphate, the thickness of the adhesive layer is greater than or equal to 70 μm and the initial tack is greater than or equal to 200 N / m; or, when the active material is lithium nickel cobalt manganese oxide, the thickness of the adhesive layer is greater than or equal to 50 μm and the initial tack is greater than or equal to 150 N / m; or, when the active material is lithium cobalt oxide, the thickness of the adhesive layer is greater than or equal to 35 μm and the initial tack is greater than or equal to 100 N / m; or, when the active material is graphite and / or silicon-based materials, the thickness of the adhesive layer is greater than or equal to 20 μm and the initial tack is greater than or equal to 60 N / m. This is more conducive to ensuring that the thickness of the active layer removed in each peeling process of electrode sheets with different compositions is between 8 μm and 12 μm, improving the accuracy of the adhesive dispersion in the test electrode sheet.
[0053] For example, when the active material is lithium iron phosphate, the thickness of the adhesive layer can be 70 μm, 75 μm, 80 μm, 85 μm, 90 μm or any combination thereof; the initial tack of the adhesive layer can be 200 N / m, 210 N / m, 220 N / m, 230 N / m, 240 N / m, 250 N / m, 260 N / m or any combination thereof.
[0054] For example, when the active material is lithium nickel cobalt manganese oxide, the thickness of the adhesive layer can be 50 μm, 55 μm, 60 μm, 70 μm or any combination thereof; the initial tack of the adhesive layer can be 150 N / m, 160 N / m, 170 N / m, 180 N / m, 190 N / m, 200 N / m or any combination thereof.
[0055] For example, when the active material is lithium cobalt oxide, the thickness of the adhesive layer can be 35 μm, 40 μm, 45 μm, 50 μm or any combination thereof; the initial tack of the adhesive layer can be 100 N / m, 110 N / m, 120 N / m, 130 N / m, 140 N / m, 150 N / m or any combination thereof.
[0056] For example, when the active material is graphite and / or silicon-based material, the thickness of the adhesive layer can be 20 μm, 25 μm, 30 μm, 35 μm or any combination thereof; the initial tack of the adhesive layer can be 60 N / m, 70 N / m, 80 N / m, 90 N / m, 100 N / m or any combination thereof.
[0057] Specifically, the initial tack of the adhesive layer can be understood as the ability of the adhesive layer to adhere instantly upon slight, momentary contact with the surface of the active layer without applying pressure.
[0058] In this embodiment of the invention, the thickness of the adhesive layer can be measured by the following method: take the above-mentioned tape, measure the thickness of the tape as A1, then scrape off the adhesive layer on the tape, measure the thickness of the substrate as A0, then the thickness of the adhesive layer = A1 - A0, wherein the thickness can be measured by a thickness gauge.
[0059] In this embodiment of the invention, the initial tack of the adhesive layer can be measured by the following method: Take the above-mentioned tape, bond the adhesive layer to the steel plate to obtain a test sample, and perform a peel test using a universal tensile testing machine. Clamp both ends of the sample in the upper and lower clamps of the tensile testing machine, and perform a peel test at a constant tensile speed. The tensile force value during the peel process is collected in real time by the equipment to obtain a tensile force-displacement curve. The average value of the stable peel tensile force data is the initial tack of the adhesive layer.
[0060] In some embodiments, when the active material is lithium iron phosphate, the thickness of the adhesive layer is 70 μm to 90 μm, and the initial tack of the adhesive layer is 200 N / m to 260 N / m; or, when the active material is lithium nickel cobalt manganese oxide, the thickness of the adhesive layer is 50 μm to 70 μm, and the initial tack of the adhesive layer is 150 N / m to 200 N / m; or, when the active material is lithium cobalt oxide, the thickness of the adhesive layer is 35 μm to 50 μm, and the initial tack of the adhesive layer is 100 N / m to 150 N / m; or, when the active material is graphite and / or silicon-based materials, the thickness of the adhesive layer is 20 μm to 35 μm, and the initial tack of the adhesive layer is 60 N / m to 100 N / m. This is more conducive to improving the accuracy of the peeling force in each peeling process and measuring the degree of adhesive dispersion in the electrode sheet.
[0061] In some embodiments, the electrode sheet is first subjected to environmental pretreatment and then subjected to n peeling processes. The environmental pretreatment includes placing the electrode sheet in a constant temperature and humidity environment for a time T, where T≥30min, wherein the temperature of the constant temperature and humidity environment is 25℃±2℃ and the relative humidity is 30%±5%.
[0062] Specifically, placing the electrode sheet in a constant temperature and humidity environment helps to eliminate the influence of moisture, internal stress, and temperature and humidity fluctuations on the peel force test, making the electrode sheet uniform and stable, and ensuring that the peel force test data is accurate, repeatable, and comparable.
[0063] For example, the placement time T can be a range of 30 min, 1 h, 1 h 30 min, 2 h, 2 h 30 min, 3 h, or any two of these; the temperature of the constant temperature and humidity environment can be a range of 23 °C, 24 °C, 25 °C, 26 °C, 27 °C, or any two of these; and the relative humidity of the constant temperature and humidity environment can be a range of 25%, 28%, 30%, 33%, 35%, or any two of these.
[0064] In this embodiment of the invention, the temperature and humidity of the constant temperature and humidity environment can be measured by a temperature and humidity sensor or a portable temperature and humidity meter.
[0065] In some embodiments, 5 ≤ n ≤ 10 is more conducive to obtaining more peel force data for each active layer, and is more conducive to reflecting the degree of migration of the adhesive from the active layer near the current collector side to the active layer away from the current collector side.
[0066] In some embodiments, the active material is lithium iron phosphate, and the areal density of the electrode sheet on one side is 170 g / m². 2 ~260g / m 2 For example, it can be 170g / m 2 180g / m 2 190g / m 2 200g / m 2 210g / m 2 220g / m 2 230g / m 2 240g / m 2 250g / m 2 260g / m 2 A range consisting of either or both of these is more conducive to increasing battery capacity.
[0067] In some embodiments, the active material is lithium nickel cobalt manganese oxide, and the areal density of the electrode sheet on one side is 160 g / m². 2 ~220g / m 2 For example, it can be 160g / m 2 170g / m 2 180g / m 2 190g / m 2 200g / m 2 210g / m 2 220g / m 2 A range consisting of either or both of these is more conducive to improving the performance of the electrode sheet.
[0068] In some embodiments, the active material is lithium cobalt oxide, and the areal density of the electrode sheet on one side is 160 g / m². 2 ~220g / m 2 For example, it can be 160g / m 2 170g / m 2 180g / m 2 190g / m 2 200g / m 2 210g / m 2 220g / m 2 A range consisting of either or both of these is more conducive to improving the cyclic and other electrochemical performance of the electrode sheet.
[0069] In some embodiments, the active material is graphite, and the surface density of the electrode sheet on one side is 90 g / m². 2 ~126g / m 2 For example, it can be 90g / m 2 100g / m 2 110g / m 2 120g / m 2 126g / m 2 A range consisting of either or both of these is more conducive to improving the cycle performance of the battery.
[0070] In some embodiments, the active material is graphite and silicon-based material, and the areal density of the electrode sheet on one side is 80 g / m². 2 ~110g / m 2 For example, it can be 80g / m 2 90g / m 2 100g / m 2 110g / m 2 A range of 1, 2, or any two of these is more conducive to improving the dispersion degree of the dispersant and enhancing the electrochemical performance of the electrode sheet, such as its cycle performance.
[0071] In this embodiment of the invention, the test process for the single-sided surface density of the electrode sheet may include: taking an electrode sheet sample, testing the total mass m1 of the electrode sheet sample, and the surface area S of one side of the electrode sheet sample in the thickness direction; then scraping off the active layer on the electrode sheet sample, testing the mass m2 of the current collector obtained, and then the single-sided surface density of the electrode sheet = (m1-m2) / S.
[0072] In this embodiment of the invention, when the active material includes one or more of lithium iron phosphate, lithium nickel cobalt manganese oxide, and lithium cobalt oxide, the electrode sheet is a positive electrode sheet. The positive electrode sheet may include a positive current collector and a positive active layer located on at least one side surface of the positive current collector. Specifically, the positive active layer may be provided on one side surface of the positive current collector, or the positive active layers may be provided on both sides of the positive current collector in the thickness direction (i.e., the two surfaces of the positive and negative positive current collector).
[0073] Specifically, lithium nickel cobalt manganese oxide may include LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811).
[0074] Specifically, the positive electrode active layer includes active materials. To distinguish them from the active materials in the negative electrode sheet, the active materials in the positive electrode active layer are collectively referred to as positive electrode active materials, and the active materials in the negative electrode active layer are collectively referred to as negative electrode active materials.
[0075] Generally, the positive electrode active layer may also include a positive electrode conductive agent and a positive electrode binder, both of which can be conventional materials in the field. For example, the positive electrode conductive agent may include one or more of conductive carbon black (SP), carbon nanotubes (CNT), acetylene black, graphene, Ketjen black, and carbon fiber; the positive electrode binder may include one or more of polyvinylidene fluoride (PVDF), polyvinyl fluoride, polyethylene, polypropylene, polyvinyl alcohol, polyvinyl chloride, carboxylated polyvinyl chloride, ethylene oxide-containing polymers, polyvinylpyrrolidone, polyurethane, etc.
[0076] Generally, in the positive electrode active layer, the mass percentage of the positive electrode active material (i.e., the ratio of the mass of the positive electrode active material to the total mass of the positive electrode active layer) can be 94% to 97%, for example, 94.0%, 94.5%, 95.0%, 95.5%, 96.0%, 96.5%, 97.0%, or any combination thereof; the mass percentage of the positive electrode conductive agent can be 0.5% to 2.0%, for example, 0.5%, 1.0%, 1.5%, 2.0%, or any combination thereof; and the mass percentage of the positive electrode binder can be 1.0% to 3.0%, for example, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, or any combination thereof.
[0077] The embodiments of the present invention may employ conventional positive current collectors in the art, for example, positive current collectors may include aluminum foil.
[0078] In this embodiment of the invention, the negative electrode sheet includes a negative electrode current collector and a negative electrode active layer located on at least one side surface of the negative electrode current collector. Specifically, the negative electrode active layer can be provided on one side surface of the negative electrode current collector, or negative electrode active layers can be provided on both opposite sides of the negative electrode current collector in the thickness direction.
[0079] Specifically, the negative electrode active layer may also include a negative electrode conductive agent and a negative electrode binder, both of which can be conventional materials in the field. For example, the negative electrode conductive agent may include one or more of conductive carbon black (SP), single-walled carbon nanotubes (SWCNT), acetylene black, graphene, Ketjen black, and carbon fiber; the negative electrode binder may include one or more of sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyacrylic acid (PAA), polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyvinyl alcohol, and sodium polyacrylate.
[0080] Generally, in the negative electrode active layer, the mass percentage of the negative electrode active material (i.e., the ratio of the mass of the negative electrode active material to the total mass of the negative electrode active layer) can be 93% to 97%, for example, 93.0%, 93.5%, 94.0%, 94.5%, 95.0%, 95.5%, 96.0%, 96.5%, 97.0%, or any combination thereof; the mass percentage of the negative electrode conductive agent can be 0.5% to 2.0%, for example, 0.5%, 1.0%, 1.5%, 2.0%, or any combination thereof; and the mass percentage of the negative electrode binder can be 1.5% to 5%, for example, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, or any combination thereof.
[0081] The embodiments of the present invention may employ conventional negative electrode current collectors in the art, for example, negative electrode current collectors include copper foil.
[0082] In some embodiments, the degree of binder dispersion in the electrode sheet is determined based on R and α. Specifically, when the active material is lithium iron phosphate, if R > 4 or α > 20, it is determined that the binder in the electrode sheet has significantly floated to the surface. For example, R can be a range of 4.1, 4.3, 4.5, 5, 5.5, 6 or any two of these; α can be a range of 20.1, 20.5, 21, 23, 25, 30 or any two of these.
[0083] In some embodiments, the degree of binder dispersion in the electrode sheet is determined based on R and α. Specifically, when the active material is lithium nickel cobalt manganese oxide, it is determined that the binder in the electrode sheet is significantly floating when R > 3 or α > 25. For example, R can be a range of 3.1, 3.5, 4, 5, 8, 10 or any two of them; α can be a range of 25.1, 28, 30, 35, 40 or any two of them.
[0084] In some embodiments, the degree of binder dispersion in the electrode sheet is determined based on R and α. Specifically, when the active material is lithium cobalt oxide, if R > 2 or α > 20, it is determined that the binder in the electrode sheet has significantly floated to the surface. For example, R can be a range of 2.1, 2.2, 2.5, 2.8, 3, 3.2, 3.5, 3.8, 4, 4.2, 4.5, 5, or any two of these ranges; α can be a range of 20.1, 25, 30, 35, 40, 45, 50, or any two of these ranges.
[0085] In some embodiments, the degree of binder dispersion in the electrode sheet is determined based on R and α, specifically including: when the active material is graphite, when R > 3 or α > 7, it is determined that the binder in the electrode sheet is significantly floating. For example, R can be a range of 3.1, 3.2, 3.5, 3.8, 4, 4.2, 4.5, 5 or any two of these; α can be a range of 7.1, 10, 15, 20, 25, 30, 35, 40, 45, 50 or any two of these.
[0086] In some embodiments, the degree of binder dispersion in the electrode sheet is determined based on R and α, specifically including: the active material is graphite and silicon-based material, and when R > 2.5 or α > 8, it is determined that the binder in the electrode sheet is significantly floating. For example, R can be a range of 2.51, 3, 3.5, 4, 4.5, 5 or any two of them; α can be a range of 8.1, 10, 12, 15, 20, 25, 30, 35, 40, 45, 50 or any two of them.
[0087] Specifically, when the binder in the electrode sheet rises significantly, there is a risk of powder falling off during rolling, and the battery made from the electrode sheet is at risk of cycle failure.
[0088] In some embodiments, the degree of binder dispersion in the electrode sheet is determined based on R and α, specifically including: when the active material is lithium iron phosphate, the binder in the electrode sheet is determined to be uniformly dispersed when 1.5≤R≤4 and 7.5≤α≤20.
[0089] In some embodiments, the degree of binder dispersion in the electrode sheet is determined based on R and α. Specifically, when the active material is lithium nickel cobalt manganese oxide, and 1.2≤R≤3 and 6≤α≤25, the binder in the electrode sheet is determined to be uniformly dispersed.
[0090] In some embodiments, the degree of binder dispersion in the electrode sheet is determined based on R and α, specifically including: when the active material is lithium cobalt oxide, the binder in the electrode sheet is determined to be uniformly dispersed when 1≤R≤2 and 0.2≤α≤20.
[0091] In some embodiments, the degree of binder dispersion in the electrode sheet is determined based on R and α, specifically including: when the active material is graphite, the binder in the electrode sheet is determined to be uniformly dispersed when 1.2≤R≤3 and 1.2≤α≤7.
[0092] In some embodiments, the degree of binder dispersion in the electrode sheet is determined based on R and α, specifically including: when the active material is graphite and silicon-based material, and 1.3≤R≤2.5 and 2≤α≤8, the binder in the electrode sheet is determined to be uniformly dispersed.
[0093] This invention also provides a method for preparing an electrode sheet, comprising the following steps:
[0094] S1. Prepare electrode sheets according to the initial process parameters;
[0095] S2. Test the degree of binder dispersion in the electrode sheet according to the above-mentioned test method for the degree of binder dispersion in the electrode sheet;
[0096] S3. When the active material is lithium iron phosphate, if R > 4 or α > 20, adjust the process parameters and prepare the electrode sheet according to the adjusted process parameters.
[0097] Alternatively, when the active material is lithium nickel cobalt manganese oxide, if R > 3 or α > 25, the process parameters are adjusted, and the electrode sheet is prepared according to the adjusted process parameters.
[0098] Alternatively, when the active material is lithium cobalt oxide, if R > 2 or α > 20, the process parameters are adjusted, and the electrode sheet is prepared according to the adjusted process parameters.
[0099] Alternatively, when the active material is graphite, if R > 3 or α > 7, the process parameters are adjusted, and the electrode sheet is prepared according to the adjusted process parameters.
[0100] Alternatively, when the active material is graphite or silicon-based material, if R > 2.5 or α > 8, the process parameters are adjusted, and the electrode sheet is prepared according to the adjusted process parameters.
[0101] S4. Repeat steps S1 to S3 until the prepared electrode sheet meets the following requirements:
[0102] When the active material is lithium iron phosphate, the prepared electrode sheet has R≤4 and α≤20.
[0103] Alternatively, when the active material is lithium nickel cobalt manganese oxide, the prepared electrode sheet has R≤3 and α≤25;
[0104] Alternatively, when the active material is lithium cobalt oxide, the prepared electrode sheet has R≤2 and α≤20;
[0105] Alternatively, when the active material is graphite, the prepared electrode sheet has R≤3 and α≤7;
[0106] Alternatively, when the active material is graphite or silicon-based, the prepared electrode sheet has R ≤ 2.5 and α ≤ 8.
[0107] According to the inventors' research, the above-mentioned electrode preparation method is more conducive to quickly adjusting the initial process parameters and reducing the risks of electrode powder shedding during rolling, interface lithium deposition, and decreased battery cycle performance.
[0108] In some embodiments, process parameters including one or more of electrode sheet areal density, coating speed, coating negative pressure air frequency, and baking temperature are more conducive to controlling the degree of binder dispersion in the electrode sheet while maintaining the battery capacity.
[0109] In this embodiment of the invention, in steps S1 and S3, an electrode sheet is prepared according to process parameters. When the electrode sheet is a positive electrode sheet, it can be specifically prepared by a coating method. Specifically, the components used to form the positive electrode active layer, such as the positive electrode active material, positive electrode conductive agent, and positive electrode binder, can be dispersed in a solvent, such as N-methylpyrrolidone (NMP), to prepare a positive electrode slurry. This slurry is then coated onto the surface of the positive electrode current collector at a set coating speed. After drying (using a set drying temperature) and rolling, a positive electrode sheet with a certain areal density is obtained. The coating, drying, and rolling processes involved are conventional operations for preparing positive electrode sheets using the coating method and are not particularly limited.
[0110] In this embodiment of the invention, in steps S1 and S3, electrode sheets are prepared according to process parameters. When the electrode sheet is a negative electrode sheet, it can be specifically prepared by coating. Specifically, the components used to form the negative electrode active layer, such as negative electrode active material, negative electrode conductive agent, and negative electrode binder, can be dispersed in a solvent, such as water (specifically deionized water), to prepare a negative electrode slurry. Then, the slurry is coated onto the surface of the negative electrode current collector at a set coating speed. After drying (using a set drying temperature) and rolling, a negative electrode sheet with a certain areal density is obtained. The coating, drying, and rolling processes involved are conventional operations for preparing negative electrode sheets using the coating method and are not particularly limited.
[0111] This invention also provides a method for evaluating battery cycle performance, comprising the following steps: testing the degree of binder dispersion in the electrode sheet according to the above-described test method; and determining the capacity retention rate of the battery after 500 cycles using the following formula:
[0112] When the positive electrode active material is lithium iron phosphate and the negative electrode active material is graphite (where R and α are both lower limits, R=1.2, α=1.2): the capacity retention rate after 500 cycles is y1=k1×R+A1 (R is the degree of binder dispersion in the lithium iron phosphate electrode F1 / F n (obtained), where k1 is -2.2 ~ -1.7, and A1 is 99.8 ~ 101.5;
[0113] Alternatively, when the positive electrode active material is lithium nickel cobalt manganese oxide and the negative electrode active material is graphite (where R and α are both lower limits, R=1.2, α=1.2): the capacity retention rate after 500 cycles is y2=k2×R+A2 (where R is the degree of binder dispersion in the lithium nickel cobalt manganese oxide electrode, F1 / F).n (obtained), where k2 is -3.0 ~ -2.6, and A2 is 91.2 ~ 95.8;
[0114] Alternatively, when the positive electrode active material is lithium cobalt oxide and the negative electrode active material is graphite (where R and α are both lower limits, R=1.2, α=1.2): the capacity retention rate after 500 battery cycles is y3=k3×R+A3 (where R is the degree of binder dispersion in the lithium cobalt oxide electrode F1 / F). n (obtained), where k3 is -3.8 to -3.1, and A3 is 88.2 to 94.1;
[0115] Alternatively, when the positive electrode active material is lithium nickel cobalt manganese oxide (where R and α are both lower limits, R=1.2, α=6.0), and the negative electrode active material is silicon-based material and graphite: the capacity retention rate after 500 cycles is y4=k4R+A4 (where R is the degree of binder dispersion in the silicon-based material and graphite electrode, F1 / F...). n (obtained), where k4 is -5.5 to -4.6, and A4 is 89.7 to 94.4;
[0116] Alternatively, when the positive electrode active material is lithium iron phosphate (where R and α are both lower limits, R=1.5, α=7.5) and the negative electrode active material is graphite: the capacity retention rate after 500 battery cycles is y5=k5×R+A5 (where R is the degree of binder dispersion in the graphite electrode F1 / F). n (obtained), where k5 is -2.3 to -1.8 and A5 is 98.3 to 101.5.
[0117] It is more conducive to quickly and directly judging the battery cycle performance. Compared with conventional evaluation methods, it is not necessary to assemble the electrode sheets into a battery and perform electrochemical cycling to judge the battery cycle performance, which greatly shortens the testing cycle.
[0118] For example, k1 can be a range consisting of -2.2, -2.0, -1.8, -1.7, or any two of them; A1 can be a range consisting of 99.8, 100, 100.5, 101, 101.5, or any two of them; k2 can be a range consisting of -3, -2.8, -2.6, or any two of them; A2 can be a range consisting of 91.2, 92, 93, 94, 95, 95.8, or any two of them; k3 can be a range consisting of -3.8, -3.5, -3.1, or any two of them. The ranges are defined as follows: A3 can be 88.2, 89, 90, 91, 92, 93, 94.1, or any two of these ranges; k4 can be -5.5, -5, -4.6, or any two of these ranges; A4 can be 89.7, 90, 91, 92, 93, 94.4, or any two of these ranges; k5 can be -2.3, -2, -1.8, or any two of these ranges; A5 can be 98.3, 99, 100, 101, 101.5, or any two of these ranges.
[0119] The present application will be specifically described below through specific embodiments. These embodiments are only some embodiments of the present application and are not intended to limit the present application. Unless otherwise specified, the raw materials used in the following embodiments are all commercially available products.
[0120] Example 1
[0121] This invention provides a method for testing the degree of binder dispersion in an electrode sheet. The specific methods for preparing the electrode sheet and testing the degree of binder dispersion in the electrode sheet are as follows:
[0122] 1. Preparation of electrode sheets
[0123] Lithium iron phosphate, PVDF (HSV900), SP, and CNT were mixed in a mass ratio of 96:2:1:1, and NMP was added. The mixture was stirred until homogeneous to prepare a positive electrode slurry.
[0124] The positive electrode slurry is coated on both sides of an aluminum foil. After drying and rolling, a positive electrode active layer with a single-sided thickness of 85 μm is formed on both sides of the aluminum foil, resulting in a single-sided areal density of 200 g / m². 2 The positive electrode plate.
[0125] 2. Test method for the degree of binder dispersion in electrode sheets
[0126] S1. Take the electrode sheet prepared above, first perform environmental pretreatment on the electrode sheet and then perform n peeling processes. The environmental pretreatment includes: placing the electrode sheet in a constant temperature and humidity environment for a time T, where T is 30 min. The temperature of the constant temperature and humidity environment is 25℃±2℃ and the relative humidity is 30%±5%.
[0127] S2. Using an adhesive tape with a thickness of 70 μm and an initial tack of 200 N / m, peel the active layer on the surface of the current collector eight times along the direction from the active layer to the current collector until the thickness of the remaining active layer on the surface of the current collector is 5 μm. The peel force F1 measured in the first peel treatment and the peel force F8 measured in the eighth peel treatment are obtained. The thickness of the active layer removed in each peel treatment is 10 μm.
[0128] S3. Calculate R=F1 / F8=2.8 and peel force attenuation slope α=|(F8−F1) / (8−1)|=18.6. Determine the degree of adhesive dispersion in the electrode sheet based on R and α. Specifically, when R≥4 or α≥20, it is determined that the adhesive in the electrode sheet is significantly floating; otherwise, it is considered that the adhesive in the electrode sheet is uniformly dispersed.
[0129] Examples 2-5
[0130] The difference from Example 1 is that the thickness of the active layer, the areal density of the electrode sheet, the thickness of the adhesive layer, the initial adhesion of the adhesive layer, the thickness of the active layer removed in each peeling process, the thickness of the active layer remaining on the surface of the current collector, and the number of peeling processes are different. The remaining steps and conditions are the same as in Example 1, as detailed in Tables 1 and 2.
[0131] Example 6
[0132] The difference from Example 1 is that, in the preparation of the electrode sheet,
[0133] Lithium nickel cobalt manganese oxide (specifically NCM811), PVDF (HSV900), SP, and CNT were mixed in a mass ratio of 97:1.5:0.5:1, and NMP was added. The mixture was stirred evenly to prepare a positive electrode slurry.
[0134] The positive electrode slurry is coated on both sides of an aluminum foil. After drying and rolling, a positive electrode active layer with a single-sided thickness of 59 μm is formed on both sides of the aluminum foil, resulting in a single-sided areal density of 200 g / m². 2 The positive electrode plate.
[0135] In the test method for the degree of adhesive dispersion in the electrode sheet, the thickness of the adhesive layer, the initial tack of the adhesive layer, the thickness of the active layer removed in each peeling treatment, the thickness of the active layer remaining on the surface of the current collector, and the number of peeling treatments are different. The remaining steps and conditions are the same as in Example 1, as detailed in Tables 1 and 2.
[0136] Examples 7-10
[0137] The difference from Example 5 is that the thickness of the active layer, the areal density of the electrode sheet, the thickness of the adhesive layer, the initial adhesion of the adhesive layer, the thickness of the active layer removed in each peeling process, the thickness of the active layer remaining on the surface of the current collector, and the number of peeling processes are different. The remaining steps and conditions are the same as in Example 1, as detailed in Tables 1 and 2.
[0138] Example 11
[0139] The difference from Example 1 is that, in the preparation of the electrode sheet,
[0140] Lithium cobalt oxide, PVDF (HSV900), SP, and CNT were mixed in a mass ratio of 97:1.5:0.5:1, and NMP was added. The mixture was stirred until homogeneous to prepare a positive electrode slurry.
[0141] The positive electrode slurry is coated on both sides of an aluminum foil. After drying and rolling, a positive electrode active layer with a single-sided thickness of 85 μm is formed on both sides of the aluminum foil, resulting in a single-sided areal density of 200 g / m². 2 The positive electrode plate.
[0142] In the test method for the degree of adhesive dispersion in the electrode sheet, the thickness of the adhesive layer, the initial tack of the adhesive layer, the thickness of the active layer removed in each peeling treatment, the thickness of the active layer remaining on the surface of the current collector, and the number of peeling treatments are different. The remaining steps and conditions are the same as in Example 1, as detailed in Tables 1 and 2.
[0143] Examples 12-15
[0144] The difference from Example 9 is that the thickness of the active layer, the areal density of the electrode sheet, the thickness of the adhesive layer, the initial adhesion of the adhesive layer, the thickness of the active layer removed in each peeling process, the thickness of the active layer remaining on the surface of the current collector, and the number of peeling processes are different. The remaining steps and conditions are the same as in Example 1, as detailed in Tables 1 and 2.
[0145] Example 16
[0146] The difference from Example 1 is that, in the preparation of the electrode sheet,
[0147] Graphite, SBR (AWG101), CMC and SP are mixed in a mass ratio of 95:2:1.5:1.5, and deionized water is added. The mixture is stirred evenly to prepare a negative electrode slurry.
[0148] The negative electrode slurry was coated onto both sides of a copper foil. After drying and rolling, a negative electrode active layer with a single-sided thickness of 63 μm was formed on both sides of the copper foil, resulting in an areal density of 107 g / m². 2 The negative electrode plate.
[0149] In the test method for the degree of adhesive dispersion in the electrode sheet, the thickness of the adhesive layer, the initial tack of the adhesive layer, the thickness of the active layer removed in each peeling treatment, the thickness of the active layer remaining on the surface of the current collector, and the number of peeling treatments are different. The remaining steps and conditions are the same as in Example 1, as detailed in Tables 1 and 2.
[0150] Examples 17-22
[0151] The difference from Example 14 is that the thickness of the active layer, the areal density of the electrode sheet, the thickness of the adhesive layer, the initial adhesion of the adhesive layer, the thickness of the active layer removed in each peeling process, the thickness of the active layer remaining on the surface of the current collector, and the number of peeling processes are different. The remaining steps and conditions are the same as in Example 1, as detailed in Tables 1 and 2.
[0152] Example 23
[0153] The difference from Example 1 is that, in the preparation of the electrode sheet,
[0154] Graphite, silicon-based materials (specifically silicon-carbon composite material with a specific capacity of 1800 mAh / g), SBR (AWG101), CMC, SP, and SWCNT were mixed in a mass ratio of 86.41:9.49:2:1.5:1.5:0.1, and deionized water was added. The mixture was stirred evenly to prepare a negative electrode slurry.
[0155] The negative electrode slurry is coated on both sides of a copper foil. After drying and rolling, a negative electrode active layer with a single-sided thickness of 62 μm is formed on both sides of the copper foil, resulting in an areal density of 95 g / m². 2 The negative electrode plate.
[0156] In the test method for the degree of adhesive dispersion in the electrode sheet, the thickness of the adhesive layer, the initial tack of the adhesive layer, the thickness of the active layer removed in each peeling treatment, the thickness of the active layer remaining on the surface of the current collector, and the number of peeling treatments are different. The remaining steps and conditions are the same as in Example 1, as detailed in Tables 1 and 2.
[0157] Examples 24-27
[0158] The difference from Example 21 is that the thickness of the active layer, the areal density of the electrode sheet, the thickness of the adhesive layer, the initial adhesion of the adhesive layer, the thickness of the active layer removed in each peeling process, the thickness of the active layer remaining on the surface of the current collector, and the number of peeling processes are different. The remaining steps and conditions are the same as in Example 1, as detailed in Tables 1 and 2.
[0159] Example 28
[0160] The difference from Example 23 is that the mass ratio of graphite, silicon-based material (specifically a silicon-carbon composite material with a specific capacity of 1800 mAh / g), SBR (AWG101), CMC, SP, and SWCNT is different, specifically 80.66:14.24:2:1.5:1.5:0.1;
[0161] The remaining steps and conditions are the same as in Example 1, as detailed in Tables 1 and 2.
[0162] Example 29
[0163] The difference from Example 23 is that the mass ratio of graphite, silicon-based material (specifically, silicon-carbon composite material with a specific capacity of 1800 mAh / g), SBR (AWG101), CMC, SP, and SWCNT is different, specifically 90.15:4.75:2:1.5:1.5:0.1;
[0164] The remaining steps and conditions are the same as in Example 1, as detailed in Tables 1 and 2.
[0165] Comparative Example 1 - Comparative Example 2
[0166] The differences from Example 1 are as follows: the thickness of the adhesive layer, the initial tack of the adhesive layer, the thickness of the active layer removed in each peeling process, the thickness of the active layer remaining on the surface of the current collector, and the number of peeling processes are different, as detailed in Tables 1 and 2.
[0167] Table 1-1
[0168]
[0169] Table 1-2
[0170]
[0171] Table 2-1 Electrode Sheet Peel Force Data
[0172]
[0173] Table 2-2 Electrode Sheet Peel Force Data
[0174]
[0175] Test case
[0176] 1. Battery manufacturing
[0177] The positive electrode sheet and separator prepared in the above embodiments, and the negative electrode sheet and separator prepared in the above embodiments are stacked in sequence to obtain the battery cell. The separator is a PE separator. The specific selection of positive and negative electrode sheets is shown in Table 3.
[0178] Lithium-ion batteries are manufactured by using aluminum-plastic film-encapsulated cells, followed by baking, vacuum injection (i.e., injection of commercially available lithium-ion battery electrolyte), aging, formation charging, aging, and capacity testing.
[0179] 2. Battery cycle performance test method:
[0180] Take the lithium-ion battery prepared above, charge it at 45°C with constant current and constant voltage at 1 / 3C to the cutoff voltage (3.65V for lithium iron phosphate, 4.2V for lithium nickel cobalt manganese oxide, and 4.45V for lithium cobalt oxide), discharge it at 1 / 3C rate to 2.5V, cycle it 3 times, and record the discharge capacity of the 3rd cycle as the initial capacity E0.
[0181] The lithium-ion batteries were then charged at a constant current of 1C to the cutoff voltage (3.65V for lithium iron phosphate, 4.2V for lithium nickel cobalt manganese oxide, and 4.45V for lithium cobalt oxide), discharged at 1C to 2.5V, and cycled 500 times. The discharge capacity of the 500th cycle was taken as the cycle capacity E2.
[0182] With E 2 / E0×100% is used to evaluate the cycle performance of lithium-ion batteries. Specific data are shown in Table 3.
[0183] Table 3 Battery Composition and Performance
[0184]
[0185] Compared to Comparative Examples 1-2, the electrode sheets in Examples 1-27 include a current collector and an active layer disposed on the surface of the current collector. The active layer includes an active material. The testing method includes the following steps: performing n peeling processes on the active layer on the surface of the current collector along the direction from the active layer to the current collector until the thickness of the remaining active layer on the surface of the current collector is less than or equal to 15 μm, and obtaining the peeling force F1 measured in the first peeling process and the peeling force F2 measured in the nth peeling process. n In each peeling process, the thickness of the active layer removed is between 8 μm and 12 μm, and n ≥ 3; the peeling force difference coefficient of the active layer is obtained as R = F1 / F. n And the peel force attenuation coefficient α=|(F n -F1) / (n-1)|, the peel force difference coefficient R satisfies: 1≤R≤4, and / or, the peel force decay coefficient α satisfies: 0.2≤α≤20. This can improve the uniformity of binder dispersion in the electrode sheet, thereby improving the cycle performance of the battery.
[0186] As shown in Table 3, the capacity retention data measured after 500 battery cycles all fall within the range of the capacity retention calculation formula of this application. In other words, the battery cycle performance can be roughly judged without assembling the electrode sheets into a battery, which greatly shortens the testing cycle.
[0187] Finally, it should be noted that other embodiments of the invention will readily occur to those skilled in the art upon consideration of the specification and practice of the invention disclosed herein. This invention is intended to cover any variations, uses, or adaptations of the invention that follow the general principles of the invention and include common knowledge or customary techniques in the art not disclosed herein, and is not limited to what has been described above. Various modifications and changes can be made without departing from its scope. The scope of the invention is limited only by the appended claims.
Claims
1. An electrode sheet, characterized in that, The electrode sheet includes a current collector and an active layer disposed on the surface of the current collector. The active layer includes an active material and a binder. Along the direction from the active layer to the current collector, the active layer on the surface of the current collector is subjected to n peeling processes until the thickness of the remaining active layer on the surface of the current collector is less than or equal to 15 μm. The peeling force F1 measured during the first peeling process and the peeling force F2 measured during the nth peeling process are obtained. n In each peeling process, the thickness of the active layer removed is between 8 μm and 12 μm, and n ≥ 3; the peeling force difference coefficient of the active layer is obtained as R = F1 / F. n And the peel force attenuation coefficient α=|(F n -F1) / (n-1)|, the peel force difference coefficient R satisfies: 1≤R≤4, and / or, the peel force attenuation coefficient α satisfies: 0.2≤α≤20.
2. The electrode sheet according to claim 1, characterized in that, The surface density of the electrode sheet is 80 g / m². 2 ~260g / m 2 .
3. An electrode sheet according to claim 1 or 2, characterized in that, The active material is at least one of positive electrode active material and negative electrode active material; Preferably, the positive electrode active material includes one or more of lithium iron phosphate, lithium nickel cobalt manganese oxide, and lithium cobalt oxide; And / or, the negative electrode active material includes one or more of graphite and silicon-based materials.
4. An electrode sheet according to claim 3, characterized in that, The negative electrode active material includes the graphite and the silicon-based material, and the mass ratio of the graphite to the silicon-based material is (85~95):(5~15).
5. An electrode sheet according to claim 3, characterized in that, The active material is a positive electrode active material, where 1≤R≤4 and 0.2≤α≤20.
6. An electrode sheet according to claim 3, characterized in that, The active material is a negative electrode active material, with 1.2≤R≤4 and 1.2≤α≤8.
7. An electrode sheet according to claim 3, characterized in that, The active material is a positive electrode active material, and the surface density of the electrode sheet is 160 g / m². 2 ~260g / m 2 .
8. An electrode sheet according to claim 3, characterized in that, The active material is a negative electrode active material, and the surface density of the electrode sheet is 80 g / m². 2 ~160g / m 2 .
9. A battery, characterized in that, Includes the electrode sheet as described in any one of claims 1 to 8.
10. A battery according to claim 9, characterized in that, The electrode sheet is at least one of a positive electrode sheet and a negative electrode sheet. The positive electrode sheet includes a positive active layer, and the positive active layer includes a positive active material. The negative electrode sheet includes a negative active layer, and the negative active layer includes a negative active material. When the positive electrode active material is lithium iron phosphate and the negative electrode active material is graphite: the capacity retention rate of the battery after 500 cycles is y1 = k1 × R1 + A1, where k1 is -2.2 ~ -1.7, R1 is the peeling force difference coefficient of the positive electrode active layer, and A1 is 99.8 ~ 101.5; Alternatively, when the positive electrode active material is lithium nickel cobalt manganese oxide and the negative electrode active material is graphite: the capacity retention rate of the battery after 500 cycles is y2 = k2 × R2 + A2, where k2 is -3.0 ~ -2.6, R2 is the peeling force difference coefficient of the positive electrode active layer, and A2 is 91.2 ~ 95.8; Alternatively, when the positive electrode active material is lithium cobalt oxide and the negative electrode active material is graphite: the capacity retention rate of the battery after 500 cycles is y3 = k3 × R3 + A3, where k3 is -3.8 to -3.1, R3 is the peeling force difference coefficient of the positive electrode active layer, and A3 is 88.2 to 94.
1. Alternatively, when the positive electrode active material is lithium nickel cobalt manganese oxide and the negative electrode active material is silicon-based material and graphite: the capacity retention rate of the battery after 500 cycles is y4 = k4 × R4 + A4, where k4 is -5.5 to -4.6, R4 is the peeling force difference coefficient of the negative electrode active layer, and A4 is 89.7 to 94.
4. Alternatively, when the positive electrode active material is lithium iron phosphate and the negative electrode active material is graphite: the capacity retention rate of the battery after 500 cycles is y5 = k5 × R5 + A5, where k5 is -2.3 to -1.8, R5 is the peeling force difference coefficient of the negative electrode active layer, and A5 is 98.3 to 101.5.